LAW ENFORCEMENT OF BREACH OF USE OF SEMAN PANTAN KRANJI RIVER IN BANYUMAS REGENCY - Eko Nur Setiawan; Soediro soediro; Astika Nurul Hidayah (Faculty of Law Universitas Muhammadiyah Purwokerto, 2020)
The rapid increase in population has led to an increase in demand for housing. The demand for housing is not proportional to the available land. Control of borderline violations is an effort in the context of law enforcement in accordance with existing laws and regulations. This study will discuss law enforcement efforts related to violations of the utilization of river borderlines and obstacles in controlling the use of Kranji river border violations in Purwokerto Timur District, Banyumas Regency, which is regulated in the Minister of Public Works and Public Housing (PUPR) Regulation of the Republic of Indonesia Number 28 / PRT / M / 2015 concerning Determination of River Border and Lake Border Lines. The research method used in this study is a normative juridical approach that is carried out through literature studies that examine secondary data in the form of legislation and other legal documents, as well as research results, results of studies, and other references. Normative juridical methods can be supplemented by interviews. Supervision and imposition of sanctions that have not been maximally become one of the causes of violations against the river border. (In addition) As well as the lack of public awareness and low public awareness of the laws and regulations relating to the determination of the river border so that it affects violations of the river border.Keywords: Law Enforcement, Borderline, River